SPECIFICS OF IMPLEMENTING SMART MANUFACTURING IN INDUSTRIAL SMALL AND MEDIUM-SIZED ENTERPRISES: BENEFITS AND LIMITATIONS (INNOVATIVE ECONOMY, 2024)
Hryshko N.Ye, Solodkov D.Ye, Hryshko V.M. SPECIFICS OF IMPLEMENTING SMART MANUFACTURING IN INDUSTRIAL SMALL AND MEDIUM-SIZED ENTERPRISES: BENEFITS AND LIMITATIONSPurpose. The aim of the article is to determine the mechanisms for solving the technological and technical limitations of data management during the automation of the production process at industrial enterprises, as well as the economic advantages and limitations created by the introduction of smart production at small and medium-sized industrial enterprises.Methodology of research. The theoretical and methodological basis of the research is the scientific works of leading scientists and practicing entrepreneurs regarding the features and technology of implementing smart production at industrial enterprises. The following general scientific methods were used in the research process: comparison – to study the approaches of the largest producing countries to the management and stimulation of the development of smart production; analysis and synthesis – to analyse the state of implementation of smart production at small and medium-sized industrial enterprises; abstract and logical – for expressing own assumptions and formulating conclusions, graphic – for visual illustration of the conceptual model of optimization of software and hardware of SMEs for data processing of enterprises.Findings. It has been established that the leading technologies forming the system of smart production - the industrial Internet of Things, neural networks based on artificial intelligence and blockchain technology – solve the following technological limitations that existed under the centralized server infrastructure: infrastructure overload due to the increase in the consumption of computing resources (solved as a result of optimization the speed of transaction accounting due to the introduction of artificial neural networks based on artificial intelligence); problems of stakeholder authentication and platform compatibility (solved as a result of automating registration of participants, transactions and as a result of automating the execution of transactions due to smart contracts within the framework of open blockchain technology); insufficient integrity and confidentiality of the data register as a result of compatibility and authentication problems (solved due to the technology of distributed accounting of transactions (blockchain), which allows to avoid falsification of data). It was found that the main economic advantage as a result of the implementation of the mentioned technologies within the framework of the smart production system is the possibility of mass customization of production at the level or almost at the level of the costs of standard mass production. It is specified that these technologies are appropriate for implementation by high-tech industrial enterprises producing products with high added value.Originality. The theoretical aspects of establishing direct and indirect economic benefits from the implementation of a smart production system at industrial small and medium-sized enterprises, approaches to optimizing production in the direction of product customization have gained further development.Practical value. Formulated approaches and recommendations for solving problems related to data processing during the automation of the production process - as a set of technological limitations, as well as an approach for solving technological limitations for the manufacture of customized products can be used at innovation-oriented industrial enterprises, in particular, medium and small ones.Key words: smart production, small and medium enterprises, industrial Internet of things, artificial intelligence, blockchain technology, automation, production, data processing.
Keywords: smart production; small and medium enterprises; industrial Internet of things; artificial intelligence; blockchain technology; automation; production; data processing.